Pensar a Arte rupestre através dos métodos e técnicas de registo e de representação. Uma abordagem ensaística - Sanches, Maria de Jesus (2012)
This text is an opening approach to the pre-historic and proto-historic rock-art recording and representational methods relating to the period of time spanning from the end of the nineteenth century to modern times (about 130 years). Its aim is not to describe an exhaustive research history, but rather to emphasize some aspects of the recording methods that might have interested different representations of the Prehistory and Protohistory, particularly in Western Europe and with special regard to the Iberian Peninsula and France. The concepts of discovery, experimental archaeology as well as both absolute and relative dating methods will also be observed. From a methodological viewpoint we have usually considered three periods of time. These periods are organized according to the value Paleolithic art has been given from: 1880 to 1950/60, 1950/60 to 1990 and a third period that spans from 1990 to the present day.